2016
DOI: 10.2220/biomedres.37.179
|View full text |Cite
|
Sign up to set email alerts
|

<b>Megalo-type α-1,6-glucosaccharides induce production of tumor necrosis factor α in primary macrophages via toll-like receptor 4 </b><b>signaling </b>

Abstract: The term "megalo-saccharide" is used for saccharides with ten or more saccharide units, whereas the term "oligo-saccharide" is used for saccharides containing fewer than ten monosaccharide units. Megalo-type α-1,6-glucosaccharide (M-IM) is a non-digestible saccharide and not utilized by intestinal bacteria, suggesting that ingested M-IM may encounter ileum Peyer's patches that contains immune cells such as macrophages. Macrophages are responsible for antigen incorporation and presentation during the initial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Further analysis showed that the increases in iNOS and NO were both significantly inhibited in the presence of TAK-242. Previous studies by others also showed that the inhibition of TLR-4 led to the inhibition of LPS [20] and megalo-type α-1,6-glucosaccharideinduced NO production [21]. TLR-4 inhibition also decreased immunoexpression of iNOS in the microglia of day old Wistar rats [22] and allografts [23].…”
Section: Discussionmentioning
confidence: 79%
“…Further analysis showed that the increases in iNOS and NO were both significantly inhibited in the presence of TAK-242. Previous studies by others also showed that the inhibition of TLR-4 led to the inhibition of LPS [20] and megalo-type α-1,6-glucosaccharideinduced NO production [21]. TLR-4 inhibition also decreased immunoexpression of iNOS in the microglia of day old Wistar rats [22] and allografts [23].…”
Section: Discussionmentioning
confidence: 79%
“…Journal Pre-proof Chen et al, 2001;Falconer, Mukerjea, & Robyt, 2011;Joe et al, 2016;A. Kimura, Hara, & Weeranuch, 2017;Lang et al, 2014;Leemhuis et al, 2014;Oguma & Kawamoto, 2003).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…7,8 Regarding their role in cell biology, in addition to carbohydrates serving as a source of energy and a component of cell structure, carbohydrates also play a role in host immune response by increasing response against pathogens and foreign cells. [9][10][11][12][13][14][15] The biological activities of carbohydrates are largely dependent on their structure, including factors like branching, linkage type, and molecular weight. 10 Chitosan is a well-known bioactive long-chain polysaccharide carbohydrate that is most commonly found in crab and shrimp shells.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The biological activities of carbohydrates are largely dependent on their structure, including factors like branching, linkage type, and molecular weight. 10 Chitosan is a well-known bioactive long-chain polysaccharide carbohydrate that is most commonly found in crab and shrimp shells. Chitosan is a bioactive carbohydrate whose effect on MSC differentiation has already been well characterized.…”
Section: Introductionmentioning
confidence: 99%